A Comprehensive Review on Supplementary Cementitious Materials – Progress, Environmental Impact, and Future Sustainability Challenges - Iqbal, Nimra; Ali, Shaukat; Ajmal, Maria; Nimra; Sial, Nosheen; Chaudhry, Asif Hanif (Scientific Inquiry and Review, 2025)
High-performance concrete involves the use of massive quantities of Portland cement and other Supplementary Cementitious Materials (SCMs), which add to its performance and sustainability. In this paper, the researcher examines the impacts of various SCMs on concrete and concludes that, the use of these materials with cement enhances compressive and mechanical strength. Ordinary SCMs are metakaolin, blast furnace slag, silica fume, laterite, fly ash, rice husk ash, nano-materials, blended cement, and sugarcane bagasse ash. In fresh concrete, SCMs affect the mechanical properties, which include elastic modulus development, strain of shrinkage, compressive strength, and flexural strength. The use of traditional SCMs, such as BFS and fly ash, has up until now been in use over decades and the effects of the SCMs on cement hydration and concrete performance are well documented. SCMs are important constituents of cementitious systems and the replacement of the ordinary Portland cement partially by them is a popular industrial practice. The application of SCMs also leads to the sustainability of the environment through decreased CO2 emissions. Carbon footprint can be reduced to a considerable extent by using partially replaced Portland cement with environmentally-friendly powders (fly ash, slag, rice husk ash, or metakaolin). The cement production is a highly energy-consuming process which emits high levels of CO2 throughout the process of limestone calcination, thus the integration of SCMs can help to save energy and minimize the emissions of greenhouse gases. Other than environmental advantages, SCMs enhance the durability of concrete, its strength and its resistance to chemical attack by refining its microstructure with the reaction of pozzolans. In general, the research on SCMs sums up their availability, influence on cement performance and durability, environmental impacts, and challenges of the construction sector and all points to the movement toward more sustainable concrete production